1987
DOI: 10.1111/j.1463-6409.1987.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

A redescription of the pinniped parasite Contracaecum ogmorhini (Nematoda, Ascaridoidea), with an assessment of its antiboreal circumpolar distribution

Abstract: The otariid seal parasite Contracaecum ogmorhini Johnston & Mawson, 1941 is redescribed based upon new material and the type specimens. The geographical records of this species indicate that it has an antiboreal circumpolar distribution with an isolated population on the south‐west coast of North America. The species is considered to be morphologically more similar to Contracaecum spp. from birds than to those from phocid seals: its possible evolution is commented upon. The material identified as C. osculatum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 3 publications
4
34
0
Order By: Relevance
“…Macko (1961) and Cram (1927) reported 10 pairs of precloacal papillae, but Hartwich (1964) reported 29-35 pairs of precloacal papillae. Previous authors reported a wide range of intraspecies variation with regard to the number of precloacal papillae in anisakids: 60-81 pairs in C. osculatum (FAGERHOLM, 1989), 23 -49 in C. ogmorhini (FAGERHOLM;GIBSON, 1987) and 44 -61 in Terranova galeocerdonis (TANZOLA;SARDELLA, 2006). For this reason, we can accept that the differences observed in relation to Hartwich's specimens may correspond to such intraspecies variation.…”
Section: Introductionmentioning
confidence: 50%
“…Macko (1961) and Cram (1927) reported 10 pairs of precloacal papillae, but Hartwich (1964) reported 29-35 pairs of precloacal papillae. Previous authors reported a wide range of intraspecies variation with regard to the number of precloacal papillae in anisakids: 60-81 pairs in C. osculatum (FAGERHOLM, 1989), 23 -49 in C. ogmorhini (FAGERHOLM;GIBSON, 1987) and 44 -61 in Terranova galeocerdonis (TANZOLA;SARDELLA, 2006). For this reason, we can accept that the differences observed in relation to Hartwich's specimens may correspond to such intraspecies variation.…”
Section: Introductionmentioning
confidence: 50%
“…Nematodes of the superfamily Ascaridoidea (Secernentea: Ascaridida) have been studied extensively with respect to alpha-taxonomy (e.g., Davey, 1971;Sprent, 1977Sprent, , 1978Sprent, , 1979Overstreet, 1979, 1981;Fagerholm and Gibson, 1987;Bruce and Cannon, 1990;Petter et al, 1991;Bruce et al, 1994), morphology (Snyder, 1985(Snyder, , 1989Fagerholm, 1989Fagerholm, , 1991Hugot et al, 1991;De and Dey, 1992), life cycles (Huizinga, 1967;Klöser et al, 1992;Køie and Fagerholm, 1995), geographic and host distribution (Fagerholm, 1988;Brattey and Ni, 1992;Bristow and Berland, 1992;Jensen et al, 1994), population genetic structure (Paggi et al, 1991;Anderson et al, 1993;Nascetti et al, 1993;Nadler, 1996), and host pathogenesis (Deardorff and Overstreet, 1980;Overstreet and Meyer, 1981). Many species, as juveniles or adults, are potential causative agents of disease in humans, domesticated animals, and wildlife (Beaver, 1956;Norris and Overstreet, 1976;Kazacos, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Contracaecum ogmorhini Johnston and Mawson, 1941, is a common ascaridoid nematode of otariids [1]. It has been found off all continents, but mainly in the southern hemisphere and the Pacific coast of South America [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found off all continents, but mainly in the southern hemisphere and the Pacific coast of South America [1,2]. Due to its morphological similarity with other species of the genus Contracaecum, C. ogmorhini has sometimes been considered a synonym of Contracaecum osculatum sensu stricto [3,4].…”
Section: Introductionmentioning
confidence: 99%